Co-expression of B7-H3 and LAG3 represents cytotoxicity of CD4+ T cells in humans - Tamura, Yumi; Ohki, Shun; Nagai, Haruna; Yoshizato, Rin; Nishi, Shizuki; Jin, Yuqi; Kitajima, Yasuo; Guo, Yun; Ichinohe, Tatsuo; Okada, Satoshi; Kawano, Yohei; Yasuda, Tomoharu (Frontiers in Immunology, 2025)
Recent studies have highlighted the potential contribution of CD4+ T cells with cytotoxic activity (CD4 CTLs) to anti-tumor immunity. However, their precise roles remain elusive, partly due to the absence of specific markers defining CD4 CTLs with target-killing potential in humans. We previously demonstrated that Epstein-Barr virus (EBV)-driven immortalized B cell lines efficiently induce human CD4 CTLs with cytotoxic functions comparable to cytotoxic CD8+ T cells (CD8 CTLs). Here we show that EBV-driven CD4 CTLs exhibit prolonged proliferation and sustained cytotoxicity compared with CD8 CTLs, although their cytotoxic function markedly decreased during long-term culture. Comparative transcriptomic analysis of CD4 CTLs with varying cytotoxic activities identified B7-H3 and LAG3 as surface molecules associated with highly cytotoxic CD4 CTLs. Co-expression of B7-H3 and LAG3 correlated with CD107a expression and was observed on CD4+ T cells with enhanced cytotoxic potential in a target-dependent manner but not on CD8 CTLs. Furthermore, B7-H3+LAG3+ CD4+ T cells were induced during co-culture with bone marrow cells from pediatric patients with B-cell acute lymphoblastic leukemia (B-ALL). These findings suggest that B7-H3 and LAG3 co-expression represents a characteristic feature of functional CD4 CTLs in humans, providing valuable insights into the role of CD4 CTLs in tumor immunity.